Por qué pedimos prestado - Suárez, Zuleyka (My University, 2022)
Utilizando solamente la casita de valores, se explica el concepto de resta y sus componentes exponiendo los casos que se pueden presentar y la explicación teórica de los mismos

Using only the little house of values, the concept of subtraction and its components are explained, exposing the cases that can be presented and the theoretical explanation of them.
Keywords: Valores -- Restas; Matemáticas; Aritmética; Operaciones matemáticas; Values -- Subtraction; Mathematics; Arithmetic; Mathematical operations